Laporan berjilid bagi cadangan rekabentuk dalaman bagi Quicksilver retail shop untuk Urban Surf Sdn. Bhd. di bangunan 2 tingkat, Kompleks Jeti Lumut, 32040 bandar Lumut, Perak Darul Ridzuan / Marhaini Asma Mustapa - Mustapa, Marhaini Asma (2004)
This dissertation is about the judicial process by various jurisdictions affecting Bolam principle, the traditional pillars of medical law which responds to the growing interest in medical negligence, a common form of medical malpractice. It is about medical practitioner's standard of care and the patient's autonomy.Medical practitioners are increasingly confronted by ethical issues involving the issues arising t-om the provisions of inthrmation, diagnosis and treatment in relation to duty and standard of care expected from the medical practitioners in administering patients while in their care.